Influence of sample preparation on the microstructure of tooth enamel apatite. (1st June 2015) - Kallistová, Anna; Skála, Roman; Horáček, Ivan; Miyajima, Nobuyoshi; Malíková, Radana
<x xml:space="preserve">Abstract</x> X‐ray powder diffraction and transmission electron microscopy are widely used for determination of the basic characteristics of the biological apatite structure. Many different techniques have been adopted for separation of the enamel part of the tooth for use in these analytical methods, but their influence on the sample itself has not yet been studied. In this paper, six different preparation techniques have been applied on pigs' teeth to see their effect on the microstructure of dental hydroxyapatite. Although the only inorganic component of the tooth is the hydroxyapatite, new phases, such as calcite, aragonite, calcium hydrogen phosphate and calcium carbonate hydroxide, appeared when a drilling technique or deproteination of the sample was used. In addition, the crystallite size (especially in the c‐axis direction) varies within a wide range (330–700 Å) depending on the preparation technique. Thus, the results indicate a strong effect of the enamel separation on the phase composition and crystallite size. The method providing results most consistent with previous studies is manual disintegration.